Deschooling dan Learning Loss Pada Pendidikan Anak Usia Dini di Masa Pandemi Covid-19 - Ndeot, Felisitas Ndeot (PERNIK : Jurnal Pendidikan Anak Usia Dini, 2021)
This paper aims to provide a description to education practitioners, parents, and observers of early childhood education and all stakeholders regarding Ivan Illich's views on deschooling which are expected to be adapted to change views about learning in students, especially in stimulating early childhood development. This paper also describes the learning loss that occurred during the Covid-19 pandemic in students, especially in early childhood due to the lack of parental competence when guiding children to study at home which causes less optimal stimulation in early childhood. Thus, the creativity of early childhood education teachers, the willingness of parents to continue to find appropriate methods in guiding and accompanying children in stimulating development at home, expected to be able to learn situation during the covid-19 pandemic.